Twelve-month prevalence, comorbidity and correlates of mental disorders in Germany: the Mental Health Module of the German Health Interview and Examination Survey for Adults (DEGS1-MH) - Jacobi, Frank; Höfler, Michael; Siegert, Jens; Mack, Simon; Gerschler, Anja; Scholl, Lucie; Busch, Markus A.; Hapke, Ulfert; Maske, Ulrike; Seiffert, Ingeburg; Gaebel, Wolfgang; Maier, Wolfgang; et al. (International journal of methods in psychiatric research, 2014)
This paper provides up to date prevalence estimates of mental disorders in Germany derived from a national survey (German Health Interview and Examination Survey for Adults, Mental Health Module [DEGS1‐MH]). A nationally representative sample (N = 5318) of the adult (18–79) population was examined by clinically trained interviewers with a modified version of the Composite International Diagnostic Interview (DEGS‐CIDI) to assess symptoms, syndromes and diagnoses according to DSM‐IV‐TR (25 diagnoses covered). Of the participants 27.7% met criteria for at least one mental disorder during the past 12 months, among them 44% with more than one disorder and 22% with three or more diagnoses. Most frequent were anxiety (15.3%), mood (9.3%) and substance use disorders (5.7%). Overall rates for mental disorders were substantially higher in women (33% versus 22% in men), younger age group (18–34: 37% versus 20% in age group 65–79), when living without a partner (37% versus 26% with partnership) or with low (38%) versus high socio‐economic status (22%). High degree of urbanization (> 500,000 inhabitants versus < 20,000) was associated with elevated rates of psychotic (5.2% versus 2.5%) and mood disorders (13.9% versus 7.8%). The findings confirm that almost one third of the general population is affected by mental disorders and inform about subsets in the population who are particularly affected. Copyright © 2014 John Wiley & Sons, Ltd.